2016
DOI: 10.1007/s12264-016-0011-3
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Genome-Wide Association Studies in Alzheimer’s Disease

Abstract: Genome-wide association studies (GWASs) have revealed a plethora of putative susceptibility genes for Alzheimer's disease (AD). With the sole exception of the APOE gene, these AD susceptibility genes have not been unequivocally validated in independent studies. No single novel functional risk genetic variant has been identified. In this review, we evaluate recent GWASs of AD, and discuss their significance, limitations, and challenges in the investigation of the genetic spectrum of AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(45 citation statements)
references
References 75 publications
1
44
0
Order By: Relevance
“…There is a high degree of overlap between functional gene categories because of pleiotropic actions of molecules on behavior. The array was subsequently complemented with the addition of variants in candidate genes (24 SNPs) that have been previously associated with increased risk of LOAD [44] and variants in candidate genes (seven SNPs) reported as associated with episodic memory performance [11] , [12] , [13] , [19] .…”
Section: Methodsmentioning
confidence: 99%
“…There is a high degree of overlap between functional gene categories because of pleiotropic actions of molecules on behavior. The array was subsequently complemented with the addition of variants in candidate genes (24 SNPs) that have been previously associated with increased risk of LOAD [44] and variants in candidate genes (seven SNPs) reported as associated with episodic memory performance [11] , [12] , [13] , [19] .…”
Section: Methodsmentioning
confidence: 99%
“…In addition, genetic factors for the development of dementia have also been examined, with the apolipoprotein E ( APOE ) genotype being identified as the most potent genetic risk factor for the development of AD [ 6 , 7 ]. Moreover, large-scale genome-wide association studies conducted mainly in Europe and the USA have identified several AD-susceptible genes, including the CR1 and CLU genes [ 7 9 ]. On the other hand, lifestyles and genetic backgrounds are known to differ among different countries or ethnicities.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from these, several other genes were found to be associated with LOAD but not much information on their roles is available so far. Reports on specific studies have been summarized by Bertram and Tanzi [73], Tosto and Reitz [74] and recently by Shen and Jia [75].…”
Section: Gwas In Alzheimer's Diseasementioning
confidence: 99%